APAKAH PERTUMBUHAN PENDUDUK BERDAMPAK BAGI PERTUMBUHAN EKONOMI KABUPATEN SOLOK - Wirda, Fisla; Putra, Trimardi Jaya; Wardani, Rahmi; Herizon, Herizon (IAIN Ambon, 2023)
AbstractsThis study analyzes the effect of population growth on economic growth in the Solok district. The data used in this study is secondary data in the form of economic growth and population growth of Solok Regency from 2011 to 2022. This data was released by the Central Statistics Agency (BPS) of Solok Regency. Data analysis was performed using simple Regression. The results showed that: Y=-2.158